(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Ginger is the most important and extensively grown spices crop in the world India has largest area under ginger cultivation in the world and ranks second in the production after China. Ginger belongs to Zingibareaceae family and is originated from South East Asia. Tropical areas having high rainfall and hot humid weather conditions are favourable for ginger. The name ginger is derived from the Baba baba Sanskrit word Yeahsran gaveram which means horn root. In South East Asia, the most popular from off ginger is raw ginger it is reward as one of the most important and valued spices off the world for over 5000 years ginger has been recognised as the universal medicine by the ancient orientates of China and India. Today ginger remains key component off more than 50 per cent of the traditional herbal remedies and has been used to trip nausea indigestion, fever and infection and to promote vitality and longevity. Ginger contains 2-3 per cent carbohydrate and a good source of calcium, iron and vitamin. Ginger is one of mainstay in India spice account and has been used for flavouring and medicinal purposes. Ginger occupies 4th position among spices produced in India, 5th position in terms of quality and 6th position in export earning among spices. India has also imported significant quantities of ginger in virus forms, viz., ginger fresh, ginger unbleached, ginger bleached, ginger powder (not elsewhere specified) including dried ginger to the ton 12,807 tons valued at 1925 lack in 2009-10. Nepal has been our main source of import